Level of Acceptance Towards Industrialised Building System (IBS) In Malaysia - Yahya, Muhamad Azani; Shafie, Muhamad Nur Safwan (International Journal of Sustainable Construction Engineering and Technology, 2012)
Construction practices towards conventional method is still being practiced widely even there were many researchers have done the studies on the inefficient of that method. On the other view, innovative construction had been the solution to improve the construction process flow. The need for innovation in construction industry is to enhance the efficiency for the success of project delivery. This could change the paradigm of norm construction practice which depends on conventional methods and a lot of non-value adding activities occur on that process flow. Industrialised Building System (IBS) is a method introduced to Malaysian construction players and it seem significance to the industry. This concept creates a new improvement for the successes of construction project by emerging techniques and materials in efficient way. This study shows the level of acceptance toward IBS concept comparing with conventional method. Interviews and questionnaires survey were done in getting data and analysed to get the factors relating time reduction, wastage and barriers of implementing it. Result shown the perception of construction players for IBS and it will provide to all parties the credits in choosing IBS concept for the project.